THE PRINCIPAL’S STRATEGY FOR MOTIVATING TEACHERS’ SELF-DIRECTED LEARNING AT SD IT RAUDHATUL JANNAH IN TALANG UBI DISTRICT, PALI REGENCY - Parasih Parasih; Ahmad Zainuri; Nyayu Soraya; Zainal Berlian (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to analyze the principal’s strategies in motivating teachers’ self-directed learning at SD IT Raudhatul Jannah, Talang Ubi District, PALI Regency. This research employed a qualitative approach using a descriptive method. Data were collected through observation, in-depth interviews, and documentation studies. The research informants included the principal, teachers, the school committee, and educational staff. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that the principal’s strategies in motivating teachers’ self-directed learning are implemented systematically based on Maslow’s hierarchy of needs. The fulfillment of physiological needs is carried out by creating a comfortable and supportive working environment. Safety needs are addressed through a supportive psychological climate, open communication, and a family-oriented working relationship. Social needs are fulfilled through the development of a collaborative culture, teacher forums, and professional learning communities. Esteem needs are met through material and non-material appreciation, which enhances teachers’ self-confidence and intrinsic motivation. Furthermore, self-actualization needs are reflected in teachers’ increased awareness, initiative, innovation, and continuous reflection in self-directed learning. Supporting factors include supportive and visionary leadership, a conducive school culture, adequate facilities, and teachers’ commitment to professionalism. Meanwhile, inhibiting factors consist of limited time due to administrative workload, differences in technological literacy, and the suboptimal follow-up of training outcomes.